2020
DOI: 10.3389/fmicb.2020.01584
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Potential Mechanism of Panobinostat in Combination With Fluconazole Against Candida albicans

Abstract: Su et al. Synergistic Antifungal Effect of Panobinostat in drug resistance, was found to be inhibited, and metacaspase which is related to cell apoptosis was activated (p < 0.01), whereas the synergistic effects were proven not to be related to the efflux pumps (p > 0.05). These findings might provide novel insights into the antifungal drug discovery and the treatment of candidiasis caused by C. albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Maximum values of six and eight for the combination of 3′-HC + 2-HC and 2-HC + FCZ, as well as isolated substances and for the lipid carriers LC (1) and LC (2), were observed, demonstrating that these combinations did not show toxicity and that they may be promising in the treatment of VVC. Similar studies have demonstrated the effectiveness of the agreement model in the evaluation of drugs combined with fluconazole (FCZ) against C. albicans [82].…”
Section: Discussionmentioning
confidence: 68%
“…Maximum values of six and eight for the combination of 3′-HC + 2-HC and 2-HC + FCZ, as well as isolated substances and for the lipid carriers LC (1) and LC (2), were observed, demonstrating that these combinations did not show toxicity and that they may be promising in the treatment of VVC. Similar studies have demonstrated the effectiveness of the agreement model in the evaluation of drugs combined with fluconazole (FCZ) against C. albicans [82].…”
Section: Discussionmentioning
confidence: 68%
“…To assess whether standardization of the G. mellonella rearing process leads to healthier larvae, the survival of standardized reared larvae was compared with that of commercially bred larvae purchased from Kreca Ento‐Feed (Ermelo, The Netherlands). To this end, a survival assay was carried out using two C. albicans reference strains (CBS562 and CBS6431), which were previously shown to be virulent in G. mellonella (Frenkel et al, 2016; Cotter et al, 2000; Romera et al, 2020; Su et al, 2020). In a dose–response assay, a range of inoculum concentrations of both strains was injected to groups of larvae, to determine how many cells are needed to kill at least 50% of the larvae (LD 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…In C. albicans , HDAC is related to fungal pathogenicity and virulence, especially in the aspect of drug resistance. Studies have shown that HDAC inhibitors in combination with azoles against drug-resistant C. albicans showed synergistic effects in vitro , and histone deacetylation modification may be one of the upstream resistant mechanisms of C. albicans ( Su et al, 2020b ). The study of modification in Aspergillus will improve our understanding of the pathogenic fungus Aspergillus and provide a theoretical foundation for the prevention and management of fungi.…”
Section: Histone Deacetylasesmentioning
confidence: 99%